2000
DOI: 10.1097/00002030-200012010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular restoration in HIV infected persons treated with abacavir and a protease inhibitor: age inversely predicts naive CD4 cell count increase

Abstract: Higher baseline levels of HIV-1 replication determine the magnitude of first phase CD4 cell increases after suppression of HIV-1 replication. Second phase (primarily naive) CD4 cell increases are not related to HIV-1 replication but are inversely relate to age suggesting that thymic potential is a major determinant of long term cellular restoration in HIV-1 infected persons receiving antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 30 publications
10
39
3
1
Order By: Relevance
“…Older participants were predicted to have a higher CD4/CD8 ratio during ART. This is inconsistent with previous reports, which suggested that older HIV-infected people have a worse immune recovery [24,25]. This analysis was biased by the narrow age range in our cohort (only 9 people aged >50 years), which might have affected our ability to determine the effect of older age on CD4/CD8 ratio.…”
Section: Discussioncontrasting
confidence: 99%
“…Older participants were predicted to have a higher CD4/CD8 ratio during ART. This is inconsistent with previous reports, which suggested that older HIV-infected people have a worse immune recovery [24,25]. This analysis was biased by the narrow age range in our cohort (only 9 people aged >50 years), which might have affected our ability to determine the effect of older age on CD4/CD8 ratio.…”
Section: Discussioncontrasting
confidence: 99%
“…The response to IL-7 may depend on thymic function and age. Reconstitution of naive T cells with ART is decreased in older HIV ϩ patients, 44 and a relation between T-cell counts and IL-7 in patients with low thymic volume has been observed. 45 It has also been shown that T-cell responsiveness to IL-7 may be impaired by HIV infection 34 because of overstimulation and desensitization of the pSTAT5 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…13 The second phase of CD4 ϩ T-cell increase, of about 5 to 10 cells/L monthly, lasts until the end of the second year of therapy, and the third phase, of about 2 to 5 cells/L monthly, extends beyond this second year for at least 7 years. 10,12,[14][15][16] Various mechanisms account for the rise in mostly naive CD4 ϩ T cells 12,17 during these 2 phases: first, de novo production of T lymphocytes by the thymus; second, the homeostatic proliferation of the residual CD4 ϩ T cells, and third, the extension of CD4 ϩ T-cell half life, a mechanism responsible for sustaining the number of naive CD4 ϩ T cells in older individuals in whom thymic production is impaired. 18 From a qualitative point of view, these 3 mechanisms of reconstitution are not equivalent.…”
Section: Immunologic Responses To Haart: Both Quality and Quantity Mamentioning
confidence: 99%